On the implementation of hybrid energy storage for range and battery life extension of an electrified Tuk-Tuk. (February 2022) - Karunarathne, Eshan; Wijesekera, Anjana; Samaranayake, Lilantha; Binduhewa, Prabath; Ekanayake, Janaka
Highlights: A novel technical solution based on a hybrid energy storage system (HESS) is proposed for 2 and 3 wheelers. The proposed solution enhances the sustainability of these vehicles by relieving range anxiety and enriching battery life. Both computer and experimental simulation study, which are in well agreement, of the proposed study is presented. HESS-equipped three-wheeler improves SoC by 6% in the drive cycle concerned extending the mileage range. SOH of the battery improves 3 times with the HESS in the drive cycle concerned. Abstract: In the pathway towards the transformation of the global energy sector, electric vehicles have gained a sparkling interest owing to their ceased emissions. However, range anxiety and fast battery degradation are the most prominent deficiencies of electric vehicles, and many solutions have been proposed to surmount them. However, such solutions often contribute to additional weight, space, and cost. In this paper, we propose a battery supercapacitor hybrid energy storage system (HESS) with a novel Kalman filtration-based energy management system to preserve the battery state of charge (SoC) enabling longer range and a flattened battery state of health (SOH) function thus enabling longer battery life. The simulation results of the solution have been experimentally verified using a full-scale electrified Tuk-Tuk, i.e., an e-Wheeler. The experimental simulation results are in well agreement with the computer simulation studies. The results show a 6% improvement in the SoC and 0.005% reduction in SOH gradient on a typical Sri Lankan urban Tuk-Tuk drive cycle without compromising the performance.